Sleep Apnea and Aortic Dissection - Patrick J Hanly; David Ford (Canadian Respiratory Journal, 1995)
A 62-year-old man presented with obstructive sleep apnea, congestive heart failure and Cheyne-Stokes respiration. Further evaluation revealed a chronic dissecting aneurysm of the aorta causing vena caval obstruction. Surgical correction or the aneurysm dramatically improved ventricular function with resolution of Cheyne-Stokes respiration. Nasal continuous positive airway pressure corrected the obstructive sleep apnea and associated clinical features. The cardiopulmonary interactions between sleep apnea and aortic dissection are discussed.